(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2019)
The quality of working conditions have a direct impact on the individuals’ quality of life and level of well-being. Attention to well-being in work environments has become a matter of great interest for legislators. However, the well-being concept has not yet found a legal definition. The first commitment to achieve a global well-being strategy was made by the World Health Organisation. The European Union claims that a positive relationship between work and well-being is a necessary factor to reach greater economic and social progress, since full and quality employment is one of the main elements of economic stability and social cohesion in a country. The Italian regulatory framework consists of various legislative provisions: the importance of the workers’ good health and quality of life has generated a complex regulatory system. In the digital society the potential health risks associated with the use of IT tools and the risk of an increased overlapping between work and personal life should not be overlooked.